2005
DOI: 10.1021/ja056455b
|View full text |Cite
|
Sign up to set email alerts
|

The Predictably Elusive Form II of Aspirin

Abstract: The elusive form II of aspirin has been obtained during co-crystallization experiments with levetiracetam or acetamide, and it has been characterized by IR, DSC, HPLC, and single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
251
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(268 citation statements)
references
References 36 publications
5
251
0
12
Order By: Relevance
“…Molecular crystals have increasingly attracted great attention due to their peculiar chemical and physical properties, which make them suitable as high energy-density materials, [1][2][3] active pharmaceutical ingredients (APIs), [4][5][6] constituents of opto-electronic devices for their linear and non-linear optical properties, [7][8][9] etc.…”
mentioning
confidence: 99%
“…Molecular crystals have increasingly attracted great attention due to their peculiar chemical and physical properties, which make them suitable as high energy-density materials, [1][2][3] active pharmaceutical ingredients (APIs), [4][5][6] constituents of opto-electronic devices for their linear and non-linear optical properties, [7][8][9] etc.…”
mentioning
confidence: 99%
“…However, increasing amount of literature is also available either to describe the precipitation behavior of this drug during pre-and post-formulation stages or to illustrate the conversion from amorphous to crystalline or vice versa within the dosage form itself. Polymorphism of aspirin crystals has recently become an important issue, following reports of a second polymorph by Vishweshwar et al (15) and Almarsson et al (16). Although the two different polymorphs (form I and form II) of ASP crystals have been existed, the mysterious metastable form II (but pure and therapeutically effective one) has a tendency to grow within the crystals of stable form I as intergrowths (17).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jafari et al (22) have also investigated the capability of the gas antisolvent (GAS) process to produce the therapeutically effective aspirin particles by studying the effect of four operating parameters namely, antisolvent addition, process temperature, solute concentration, and solvent type (methanol and acetone) on the final product particle size distribution, morphology, and crystallinity. Furthermore, the elusive form II of aspirin has been obtained during co-crystallization experiments of aspirin with levetiracetam or acetamide in acetonitrile after heating this solution at 70°C followed by slow evaporation of this homogeneous solution over 2 days (15,16). Collectively, all these studies indicated that depending on the experimental conditions applied at the time of their screening/ preformulation stage, the formation of pure or therapeutically effective form of crystalline API might have been occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations